A certain justice - Lescroart, John T. (Signet Book/New American Library, 2006)
When the angry white mob poured out of the bar on San Francisco's Geary Street and surrounded an innocent black man, Kevin Shea was the only one who tried to stop them. He failed, and now, thanks to a deceptive news photo taken during the melee, he is wanted for the murder himself-and the real culprits have threatened his life if he says a word.